Anti-oxidation graphite crucible and preparation method thereof

By using 3D printing technology and impregnation method to form a silicon carbide protective layer on the graphite crucible, the problem of oxidation of graphite crucible at high temperatures is solved, and its oxidation resistance and stability are significantly improved.

CN119912261APending Publication Date: 2025-05-02NINGBO VULCAN TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411937593.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The existing graphite crucibles are prone to oxidation under high-temperature oxidative atmosphere, resulting in a decrease in mechanical properties. The existing antioxidant methods have poor stability and significantly reduced the antioxidant effect at high temperatures.

Method used

Prefabricated blanks are prepared by 3D printing technology, and their surfaces and internal pores are filled with impregnated slurry prepared by carbon powder and other raw materials. Through impregnation and curing, a dense silicon carbide layer is formed, and a reaction sintering method is used to react with silicon particles to form a stable silicon carbide protective layer.

Benefits of technology

It significantly improves the high-temperature oxidation resistance of the graphite crucible, enhances the adhesion strength and stability of the silicon carbide layer, reduces the possibility of oxidizing gas entering the inside of the material, and effectively prevents the high-temperature oxidation of the graphite crucible.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912261A_ABST
    Figure CN119912261A_ABST
Patent Text Reader

Abstract

The invention provides an antioxidant graphite crucible and a preparation method thereof.The preparation method comprises the following steps that S1, graphite powder is subjected to ball milling and sieving, and graphite composite powder with grain composition is obtained; s2, the graphite composite powder is prepared into a prefabricated blank in a 3D printing mode; s3, carbon powder, deionized water, a dispersing agent, a binder and aluminum powder are mixed, and dipping slurry is prepared; s4, impregnating the prefabricated blank in the impregnating slurry, and curing in a drying oven to obtain an impregnated blank; and S5, coating the impregnated green body with silicon particles, and carrying out high-temperature sintering to obtain the graphite crucible. The compact silicon carbide layers are formed on the inner surface and the outer surface of the graphite crucible, so that internal air holes of the graphite crucible can be filled, oxidizing gas can be prevented from entering the graphite crucible, and the effect of preventing high-temperature oxidation of the graphite crucible is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of graphite products, and in particular to an anti-oxidation graphite crucible and a preparation method thereof. Background Art

[0002] Graphite crucible is a crucible made of graphite as the main raw material. It has the advantages of high temperature resistance, strong thermal conductivity, good corrosion resistance and long service life. It is widely used in the smelting of non-ferrous metals and their alloys.

[0003] However, graphite materials are very easy to oxidize in a high-temperature oxidizing atmosphere, and graphite crucibles usually work in an oxidizing atmosphere. Oxidation weight loss will cause the mechanical properties of the material to be greatly reduced. In order to prevent the oxidation of the graphite crucible, the prior art proposes to form an anti-oxidation layer on the surface of the graphite crucible by an impregnation method. For example, patent document CN202211672659.2 discloses a method of using SiC-Y2O3 slurry to impregnate a transition layer on the surface of a graphite crucible, and then using polyvinyl alcohol to assist in forming a SiC coating. However, the coating obtained by this method has poor stability and faces the problem of volatilization of the impregnant at high temperatures, resulting in a significant reduction in the antioxidant effect. Summary of the invention

[0004] In view of the shortcomings of the prior art, the technical problem to be solved by the present invention is how to prevent the high-temperature oxidation of the graphite crucible and improve the stability of the anti-oxidation layer.

[0005] In order to solve the above problems, the present invention provides a method for preparing an oxidation-resistant graphite crucible, comprising the following steps:

[0006] S1. Ball-milling and sieving the graphite powder to obtain a graphite composite powder with a particle size distribution;

[0007] S2, preparing a prefabricated body by 3D printing the graphite composite powder;

[0008] S3, mixing carbon powder, deionized water, dispersant, binder and aluminum powder to prepare an impregnation slurry;

[0009] S4, impregnating the prefabricated body in the impregnation slurry, and placing the prefabricated body in an oven for curing to obtain an impregnated body;

[0010] S5, coating the impregnated green body with silicon particles, and sintering at high temperature to obtain a graphite crucible.

[0011] The present invention prepares an impregnation slurry with carbon powder, and performs an impregnation treatment on a prefabricated body so that the impregnation slurry fills the pores inside the graphite material and covers its surface. Subsequently, the impregnation slurry reacts with silicon particles by a reaction sintering method to form a dense silicon carbide layer, which can not only reduce the oxidizing gas from entering the material, but also form a protective layer on the surface of the crucible body, further blocking oxygen, thereby preventing the graphite crucible from high-temperature oxidation.

[0012] Furthermore, the solid content of the impregnation slurry is 15% to 60%. The solid content of the impregnation slurry is controlled so that the impregnation slurry can enter the pores of the graphite material and adhere to the surface of the preform.

[0013] Furthermore, in the step S3, the mass ratio of the raw materials of the impregnation slurry is carbon powder: deionized water: dispersant: binder: aluminum powder = 25-60: 32-57: 2-8: 1-4: 1-3.

[0014] Furthermore, the dispersant is polyacrylamide and / or sodium polyacrylate, and the binder is methyl methacrylate and / or polyvinyl alcohol.

[0015] The impregnation slurry uses carbon powder as a main raw material, which can react with silicon particles to form a silicon carbide layer. No precious components such as Mo, Cr, Hf, etc. need to be added to the impregnation slurry, and the material cost is low.

[0016] Furthermore, in step S4, the immersion time is 20 to 240 minutes. The immersion time is controlled to ensure the pore filling and surface coating effects of the immersion slurry.

[0017] Furthermore, in step S4, the curing temperature is 150-250° C. and the curing time is 12-24 hours. After the impregnation, the impregnation slurry is cured to form a uniform impregnation coating.

[0018] Furthermore, in step S5, the sintering temperature is 1450-1600° C. The sintering temperature is controlled to allow the impregnation slurry to react with the silicon particles to form a silicon carbide protective layer.

[0019] Furthermore, in step S1, the particle size of the graphite composite powder is in the range of 50 to 250 μm. The use of the graphite composite powder with particle grading effectively improves the packing density of the powder and preserves the mechanical properties of the graphite crucible.

[0020] Furthermore, in step S2, the preform is prepared by one of laser selective sintering, stereolithography, three-dimensional printing, and direct writing. By 3D printing, a graphite crucible with a complex geometric shape and internal structure can be prepared, which helps to optimize heat conduction and reduce heat loss.

[0021] The present invention also provides an anti-oxidation graphite crucible, which is prepared by the above-mentioned preparation method and comprises a graphite crucible body, wherein the internal pores and the surface of the graphite crucible body are provided with a silicon carbide layer. The silicon carbide layer of the graphite crucible has high adhesion strength and good stability, and can significantly improve the high-temperature anti-oxidation performance of the graphite crucible. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a photo of the graphite crucible prepared in Example 1 after high temperature treatment.

[0023] Figure 2 This is a photo of the graphite crucible prepared in Comparative Example 1 after high temperature treatment. DETAILED DESCRIPTION

[0024] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. It should be noted that the following embodiments are only used to illustrate the implementation method and typical parameters of the present invention, and are not used to limit the parameter range described in the present invention. Reasonable changes derived therefrom are still within the scope of protection of the claims of the present invention.

[0025] It should be noted that the endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.

[0026] The embodiment of the present invention provides an anti-oxidation graphite crucible and a preparation method thereof. The anti-oxidation graphite crucible includes a graphite crucible body, the main material of which is graphite. A dense silicon carbide layer is provided in the internal pores and on the surface of the graphite crucible body. The silicon carbide layer can block oxygen and prevent the graphite material from being oxidized at high temperature.

[0027] The preparation method of the above-mentioned graphite crucible comprises the following steps:

[0028] S1. Preparing graphite composite powder: ball-milling and sieving graphite powder to obtain graphite composite powder with particle size distribution.

[0029] In a specific embodiment, graphite powder is put into a ball mill for ball milling, the ball mill speed is 100-150r / min, the ball-to-material ratio is (2-3): 1, and the ball milling time is 2-3 hours; after ball milling, the graphite composite powder is sieved with a 60-300 mesh screen, and the particle size range of the graphite composite powder is 50-250μm. The use of a particle-graded graphite composite powder can effectively increase the bulk density of the powder and preserve the mechanical properties of the graphite crucible.

[0030] S2, prefabricated body forming: the graphite composite powder obtained in step S1 is used to prepare a prefabricated body by 3D printing.

[0031] In a specific embodiment, the 3D printing molding method may be selected from laser selective sintering (SLS), stereolithography (SLA), three-dimensional printing (3DP), direct writing (DIW), etc.; the 3D printing molding method is followed by drying, the drying temperature is 100 to 200° C., and the drying time is 10 to 15 hours.

[0032] S3. Prepare impregnation slurry: mix carbon powder, deionized water, dispersant, binder and aluminum powder to prepare impregnation slurry.

[0033] In a specific embodiment, the dispersant may be polyacrylamide, sodium polyacrylate, etc.; the binder may be methyl methacrylate, polyvinyl alcohol, etc. The solid content of the impregnation slurry is controlled to be 15% to 60% to ensure the impregnation effect. Preferably, the mass ratio of each raw material of the impregnation slurry is carbon powder: deionized water: dispersant: binder: aluminum powder = 25 to 60: 32 to 57: 2 to 8: 1 to 4: 1 to 3. Step S3 can be performed simultaneously with steps S1 and S2.

[0034] S4, prefabricated body impregnation: the prefabricated body obtained in step S2 is impregnated in the impregnation slurry obtained in step S3, and placed in an oven for curing to obtain an impregnated body.

[0035] In a specific embodiment, the impregnation time is 20 to 240 minutes, so that the impregnation slurry covers the surface of the preform and enters the pores of the graphite material. The curing temperature is 150 to 250° C., the curing time is 12 to 24 hours, and the impregnation slurry forms a uniform impregnation coating after curing.

[0036] S5, reaction sintering: the impregnated body obtained in step S4 is coated with silicon particles and subjected to high temperature sintering to obtain a graphite crucible.

[0037] In a specific embodiment, the impregnated body is surrounded by silicon particles and wrapped with graphite paper. The sintering temperature is 1450-1600° C., so that the impregnated slurry reacts with the silicon particles to form a silicon carbide protective layer.

[0038] The above preparation method is based on the principle of composite graphite powder, and adopts 3D printing molding technology to prepare a preform. The preform is impregnated in an impregnation slurry with carbon powder, so that the impregnation slurry covers the surface of the preform and fills the pores inside the graphite material. Then, a reaction sintering method is used to react with silicon particles to form a silicon carbide layer with high adhesion strength and good stability. This not only reduces the entry of oxidizing gases into the material, but also forms a protective layer on the surface of the crucible body to further block oxygen, thereby significantly improving the high-temperature oxidation resistance of the graphite crucible.

[0039] The technical solutions and effects of the present invention are further described below in conjunction with specific embodiments.

[0040] Example 1

[0041] (1) Putting graphite powder into a ball mill for ball milling, the ball mill speed is 150r / min, the ball-to-material ratio is 2:1, and the ball milling time is 3 hours; after ball milling, sieving with a 60-300 mesh sieve to obtain a graphite composite powder with a particle size distribution, and the particle size range of the graphite composite powder is 50-250μm.

[0042] (2) 200 g of graphite composite powder was placed in an SLS laser 3D printer for molding and dried in an oven at 100 °C for 12 h to obtain a preform.

[0043] (3) Weigh 500 g of carbon powder, 500 g of deionized water, 50 g of polyacrylamide, 20 g of methyl methacrylate, and 20 g of aluminum powder, and mix them evenly to obtain an impregnation slurry.

[0044] (4) The prefabricated body obtained in step (2) is immersed in the impregnation slurry obtained in step (2) for 60 minutes; the prefabricated body is placed in an oven at 200° C. and cured for 12 hours to obtain an impregnated body.

[0045] (5) The impregnated body obtained in step (4) is coated with silicon particles, wrapped with graphite paper, and sintered at 1500° C. for 4 hours to obtain a graphite crucible.

[0046] The graphite crucible prepared in this example was placed in a tubular furnace, air was introduced into the furnace at a flow rate of 0.2 L / min, and the furnace was heated to 1500°C and kept warm for 4 hours. Figure 1 As shown, the silicon carbide layer and the crucible body are intact.

[0047] Example 2

[0048] (1) Putting graphite powder into a ball mill for ball milling, the ball mill speed is 150r / min, the ball-to-material ratio is 2:1, and the ball milling time is 3 hours; after ball milling, sieving with a 60-300 mesh sieve to obtain a graphite composite powder with a particle size distribution, and the particle size range of the graphite composite powder is 50-250μm.

[0049] (2) 200 g of graphite composite powder was placed in an SLA 3D printer for molding and dried in an oven at 100 °C for 12 h to obtain a preform.

[0050] (3) Weigh 400 g of carbon powder, 500 g of deionized water, 30 g of sodium polyacrylate, 30 g of methyl methacrylate, and 20 g of aluminum powder, and mix them evenly to obtain an impregnation slurry.

[0051] (4) The prefabricated body obtained in step (2) is immersed in the impregnation slurry obtained in step (2) for 120 minutes; the prefabricated body is placed in an oven at 150° C. and cured for 20 hours to obtain an impregnated body.

[0052] (5) The impregnated body obtained in step (4) is coated with silicon particles, wrapped with graphite paper, and sintered at 1600° C. for 4 hours to obtain a graphite crucible.

[0053] The graphite crucible prepared in this example was placed in a tubular furnace, air was introduced into the furnace at a flow rate of 0.2 L / min, and heated to 1600° C. and kept warm for 4 h. After the high-temperature treatment, the graphite crucible was in good condition.

[0054] Example 3

[0055] (1) Putting graphite powder into a ball mill for ball milling, the ball mill speed is 150r / min, the ball-to-material ratio is 2:1, and the ball milling time is 3 hours; after ball milling, sieving with a 60-300 mesh sieve to obtain a graphite composite powder with a particle size distribution, and the particle size range of the graphite composite powder is 50-250μm.

[0056] (2) 200 g of graphite composite powder was placed in an SLS 3D printer for molding and dried in an oven at 150 °C for 12 h to obtain a preform.

[0057] (3) Weigh 300 g of carbon powder, 400 g of deionized water, 50 g of polyacrylamide, 20 g of polyvinyl alcohol, and 20 g of aluminum powder, and mix them evenly to obtain an impregnation slurry.

[0058] (4) The prefabricated body obtained in step (2) is immersed in the impregnation slurry obtained in step (2) for 240 minutes; the prefabricated body is placed in an oven at 250° C. and cured for 16 hours to obtain an impregnated body.

[0059] (5) The impregnated body obtained in step (4) is coated with silicon particles, wrapped with graphite paper, and sintered at 1450° C. for 6 hours to obtain a graphite crucible.

[0060] The graphite crucible prepared in this example was placed in a tubular furnace, air was introduced into the furnace at a flow rate of 0.2 L / min, and heated to 1600° C. and kept warm for 4 h. After the high-temperature treatment, the graphite crucible was in good condition.

[0061] Comparative Example 1

[0062] (1) Putting graphite powder into a ball mill for ball milling, the ball mill speed is 150r / min, the ball-to-material ratio is 2:1, and the ball milling time is 3 hours; after ball milling, sieving with a 60-300 mesh sieve to obtain a graphite composite powder with a particle size distribution, and the particle size range of the graphite composite powder is 50-250μm.

[0063] (2) 200 g of graphite composite powder was placed in an SLS laser 3D printer for molding and dried in an oven at 100 °C for 12 h to obtain a preform.

[0064] (3) Weigh 500 g of silicon carbide powder, 500 g of deionized water, 50 g of polyacrylamide, and 20 g of methyl methacrylate, and mix them evenly to obtain an impregnation slurry.

[0065] (4) The prefabricated body obtained in step (2) is immersed in the impregnation slurry obtained in step (2) for 60 minutes; the prefabricated body is placed in an oven at 200° C. and cured for 12 hours to obtain an impregnated body.

[0066] (5) The impregnated body obtained in step (4) is sintered at a high temperature of 1500° C. and kept warm for 4 hours to obtain a graphite crucible.

[0067] The graphite crucible prepared in this comparative example was placed in a tubular furnace, air was introduced into the furnace at a flow rate of 0.2 L / min, and heated to 1500°C for 4 hours. Figure 2 As shown, the silicon carbide layer partially fell off and the crucible body was oxidized.

[0068] Comparative Example 2

[0069] (1) Putting graphite powder into a ball mill for ball milling, the ball mill speed is 150r / min, the ball-to-material ratio is 2:1, and the ball milling time is 3 hours; after ball milling, sieving with a 60-300 mesh sieve to obtain a graphite composite powder with a particle size distribution, and the particle size range of the graphite composite powder is 50-250μm.

[0070] (2) 200 g of graphite composite powder was placed in an SLS laser 3D printer for molding and dried in an oven at 100 °C for 12 h to obtain a preform.

[0071] (3) The prefabricated body obtained in step (2) is coated with silicon particles, sintered at a high temperature of 1500° C., and kept warm for 4 hours to obtain a graphite crucible.

[0072] The graphite crucible prepared in this comparative example was placed in a tubular furnace, air was introduced into the furnace at a flow rate of 0.2 L / min, and heated to 1500° C. and kept warm for 4 hours. After high-temperature treatment, the graphite crucible underwent oxidation loss.

[0073] Although the present invention is disclosed as above, the present invention is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the scope defined by the claims.

Claims

1. A method for preparing an oxidation-resistant graphite crucible, characterized in that: The following steps are involved: S1. Ball-milling and sieving the graphite powder to obtain a graphite composite powder with a particle size distribution; S2, preparing a prefabricated body by 3D printing the graphite composite powder; S3, mixing carbon powder, deionized water, dispersant, binder and aluminum powder to prepare an impregnation slurry; S4, impregnating the prefabricated body in the impregnation slurry, and placing the prefabricated body in an oven for curing to obtain an impregnated body; S5, coating the impregnated green body with silicon particles, and sintering at high temperature to obtain a graphite crucible.

2. The method for preparing an oxidation-resistant graphite crucible according to claim 1, characterized in that: In the step S3, the solid content of the impregnation slurry is 15% to 60%.

3. The method for preparing an oxidation-resistant graphite crucible according to claim 2, characterized in that: In the step S3, the mass ratio of the raw materials of the impregnation slurry is carbon powder: deionized water: dispersant: binder: aluminum powder = 25-60: 32-57: 2-8: 1-4: 1-3.

4. The method for preparing an oxidation-resistant graphite crucible according to claim 3, characterized in that: The dispersant is polyacrylamide and / or sodium polyacrylate, and the binder is methyl methacrylate and / or polyvinyl alcohol.

5. The method for preparing an anti-oxidation graphite crucible according to any one of claims 1 to 4, characterized in that: In the step S4, the immersion time is 20 to 240 minutes.

6. The method for preparing an oxidation-resistant graphite crucible according to claim 5, characterized in that: In the step S4, the curing temperature is 150-250° C., and the curing time is 12-24 hours.

7. The method for preparing an oxidation-resistant graphite crucible according to claim 1, characterized in that: In the step S5, the sintering temperature is 1450-1600°C.

8. The method for preparing an oxidation-resistant graphite crucible according to claim 1, characterized in that: In the step S1, the particle size of the graphite composite powder is in the range of 50 to 250 μm.

9. The method for preparing an oxidation-resistant graphite crucible according to any one of claims 1 to 4, characterized in that: In the step S2, the prefabricated body is prepared by using one of laser selective sintering, stereolithography, three-dimensional printing, and direct writing.

10. An anti-oxidation graphite crucible, characterized in that: The crucible is prepared by the preparation method according to any one of claims 1 to 9, comprising a graphite crucible body, wherein the surface and internal pores of the graphite crucible body have a silicon carbide layer.

Citation Information

Patent Citations

  • A coating forming method for an isostatic graphite crucible

    CN115819119B